The evolution, characteristics, and driving forces of the rural-urban HCEs in China: based on the EIO-SDA model - Yang, Yang; Yang, Meijian; Luo, Jia; Wang, Zhengzao; Chi, Yuanying; Chen, Yahui (Frontiers in Environmental Science, 2024)
Households' carbon emissions (HCEs) plays an important role in the overall carbon emission (CE) reduction. This study conducts a comparative analysis of the trends and characteristics of the rural and urban HCEs in China in 1997–2020, by applying the environmental input-output (EIO) model. Then, a three-stage SDA model is applied to decompose the driving forces of the rural and urban HCEs evolution into population effect, per capita HCEs effect, expenditure effect, CE intensity effect, energy structure effect, and energy consumption intensity effect. It is obtained that the rural HCEs increases before 2015 and then decreases, but its per capita HCEs has always shown an upward trend. The urban HCEs has been increasing, but its per capita HCEs starts to decrease after 2015. Indirect HCEs accounts for over 80% of both the rural and urban HCEs, and Residence, Food and Tobacco, Transportation and Communication are the three biggest contributing sectors. To reveal the driving forces of the rural and urban HCEs evolution, this study conducts phase decomposition analysis with 2015 as a turning point. For rural HCEs, in 1997–2015, rural HCEs increased due to the dominant expenditure effect; from 2015 to 2020, the driving force reversed, leading to a decline in rural HCEs. For urban HCEs, the positive population and expenditure effects have always been larger than the negative energy structure and energy consumption intensity effects, resulting growth in urban HCEs. For urban per capita HCEs, in 1997–2015, the positive expenditure effect is greater than the negative CE intensity effect, leading to an increase in urban per capita HCEs, and a positive urban per capita HCEs effect. In 2015–2020, the driving force reversed, leading to a decline in urban per capita HCEs. Based on above results, countermeasures to promote rural and urban HCEs reduction are discussed.